The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15625/2615-9783/16502
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ionospheric irregularities over Vietnam and adjacent region for the 2008-2018 period

Abstract: This paper presents the variations of the rate of change of Total Electron Content (TEC) index (ROTI), characterizing the occurrence of ionospheric plasma irregularities over Vietnam and neighboring countries in the Southeast Asian region using the continuous GPS data during the 2008-2018 period. The results showed that the occurrence of strong ROTI in all stations is maximum in equinox months March/April and September/October and depends on solar activity. The ROTI is weak during periods of low solar activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The keograms based on CMONOC in 2014 showed that the irregularities had the highest monthly occurrence rate in March of almost 100%, then 80% in September, 48% in December and 27% in June. The high occurrence in both equinoxes and low occurrence in two solstices are consistent with previous results (Su et al 2008;Thanh et al 2021). The seasonal characteristics of occurrence rate showed good correspondence with the vertical drift velocities of the ionospheric plasma (Vyas and Dayanandan 2011;Su et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The keograms based on CMONOC in 2014 showed that the irregularities had the highest monthly occurrence rate in March of almost 100%, then 80% in September, 48% in December and 27% in June. The high occurrence in both equinoxes and low occurrence in two solstices are consistent with previous results (Su et al 2008;Thanh et al 2021). The seasonal characteristics of occurrence rate showed good correspondence with the vertical drift velocities of the ionospheric plasma (Vyas and Dayanandan 2011;Su et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Their results for 2014 showed that only at CUSV (13.74 °N, 100.53 °E) station the occurrence rate in December is higher than that in June. At MTEV (22.39 °N,102.81 °E) and SMAV (21.06 °N, 103.75 °E), the occurrence in June are larger than that in December (Thanh et al 2021). Some researchers found that the occurrence rate of VHF scintillation or spread F in the low-latitude of Indian sector peaked in the equinoxes and winter during the high solar activity period; and during the low solar activity period the occurrence peaked in equinoxes and summer (Sushil and Gwal 2000;Singh et al 2004;Vyas and Dayanandan 2011;Sahithi et al 2019;Raghunath and Ratnam 2015).…”
Section: Discussionmentioning
confidence: 92%
“…[11] Similarly, Nguyen Thi Lan Huong (2013) documented that nitrate level in Ipomoea aquatica, Brassica juncea, and Brassica integrifolia after 9 days of fertilized were 613.09, 587.08, and 580.73 mg/kg of fresh mass, respectively. [12] Table 3 * 1 Each value represents the mean ± SD of six replicates. * 2 The safe limit value set by the VMARD [13] In three leafy vegetables in this study (Brassica juncea, Brassica integrifolia, Ipomoea aquatica) were significantly higher than safe limit value set by the VMARD.…”
Section: Content Of the Nitrate Form In Leafy Vegetablesmentioning
confidence: 99%
“…The occurrence characteristics of high values of ROTI at low latitudes in Africa have been discussed by Abe et al [10], by finding the longitudinal differences of such occurrences. On the other hand, Thanh et al [11] have analysed the behaviour of ROTI over low latitudes in Southeast Asia, in order to characterize ionosphere irregularities.…”
Section: Introductionmentioning
confidence: 99%